2023
DOI: 10.5098/hmt.20.7
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study of Stagnation Point Flow of Casson Fluid Over a Continuous Moving Surface

Abstract: In this paper, we study the behavior of heat transfer of Casson fluid at the magnetohydrodynamic stagnation point with thermal radiation over a continuous moving sheet. The appropriate similarity transfer is used to transfer the governing differential equations into the ordinary differential equation and then solved by the collocation method based on spline function. The obtained results are investigated with the existing literature by direct comparison. We found that an increment in the value of the shrinking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…An important new area of mathematical modelling has emerged from the combination of fractional calculus and nonlinear partial differential equations (PDEs), providing a powerful perspective through which to understand complicated events with memory and non-local behaviours. Nonlinear partial differential equations (FPDEs) include nonlinear components and fractional derivatives, allowing non-integer order derivatives and nonlinear interactions to be described in systems 13 15 . For phenomena where memory effects, long-range interactions or anomalous diffusion are key, this combination has broad applications in many different areas, including physics, biology, engineering, and finance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An important new area of mathematical modelling has emerged from the combination of fractional calculus and nonlinear partial differential equations (PDEs), providing a powerful perspective through which to understand complicated events with memory and non-local behaviours. Nonlinear partial differential equations (FPDEs) include nonlinear components and fractional derivatives, allowing non-integer order derivatives and nonlinear interactions to be described in systems 13 15 . For phenomena where memory effects, long-range interactions or anomalous diffusion are key, this combination has broad applications in many different areas, including physics, biology, engineering, and finance.…”
Section: Introductionmentioning
confidence: 99%
“…However, these efforts greatly advance scientific knowledge and technological progress. This work starts with a detailed study of a particular class of fractional nonlinear partial differential equations, trying to find solutions that show the interesting complexity of these systems and to shed light on their special features 15 – 18 . The studies referenced cover a wide range of topics, from aerospace engineering to materials science and physics.…”
Section: Introductionmentioning
confidence: 99%
“…Bujurke et al (1998) found the series solution for the same problem. Various authors have also contributed in the analysis of Casson fluid flow [Mukhopadhyay et al (2013); Ghiasi and Saleh (2019); Kranthi ; Dhange et al (2022); Muhammad et al (2023)]. Elkouh (1967) analysed the flow between two paral- † Corresponding author.…”
Section: Introductionmentioning
confidence: 99%